SISTEM PENUNJANG KEPUTUSAN PUSAT KESEHATAN MASYARAKAT KUMUH PADAT KUMUH MISKIN BERDASARKAN DATA MINING MENGGUNAKAN DATA WAREHOUSE - Hendra, Hendra; Mulyani, Astriana (PETIR, 2019)
Designing and building a decision support system based on data mining using data warehouse, especially health centersin the villages of Kampung Rawa in ranet system development in such a way to explore the added value in the form of information that had been unknown to them manually from a database is a matter that will be discussed in this study. This research is a study of causal relationships of aset of variables to be studied. The method used in this study uses data mining techniques are then developed with the support ofthe data ware house with data retrieval from the health center's annual reportas a Decision Support System which can collect information in the formulation of analytical techniques and decision-making procedures. The experiment was conducted at the health centerin Central Jakarta Kampung Rawa. The first unit of analysis used in this study are all part of heal this in Kampung Rawa Health Center. To obtain a representative unit of analysis, in this research, the classification by category Rukun Warga denseslums and poor slum containedin RW 01, RW 02, RW 06 and RW 08.